The evolution of theoretical understanding of physical recreation in the context of history - Vakhnin N.A.; Elmurzaev M.A.; Izotov E.A.; Mayboroda E.T. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to discern the characteristics of the evolution of scientific understanding in the realm of physical recreation. Methods and structure of the study. The foundation of this research was a compilation of scholarly articles that explored the issues of physical rehabilitation. The total number of sources was 85. Results and conclusions. The theory of physical recreation is the product of merging knowledge from the fields of pedagogy, sociology, and biology. The foundations for understanding physical recreation emerged in various aspects of social practice and became a natural part of people’s daily lives. Through a historical examination, the authors have determined that the foundations for creating a scientific theory and methodology for physical recreation have now been established. Consequently, the expansion of its conceptual framework, the organization of methodological approaches, and the establishment of principles and theoretical foundations for scientific theory as a form of physical culture and physical education are now crucial.